Acoustic comfort in large railway stations. (March 2020) - Wu, Yue; Kang, Jian; Zheng, Wenzhong; Wu, Yongxiang
Highlights: Different dominant sound sources in different spaces lead to different levels of acoustic comfort. There is a significant positive correlation between subjective comfort evaluation and objective measurement of the SPL and RT. When the density of people increases, the preference for speech sounds and activity sounds decline rapidly. People have the highest preference for broadcast sound, but its intelligibility needs to be improved. Older people and people with higher incomes and education levels are more tolerant of the acoustic environment. Abstract: Large railway stations attract a wide range of passengers and citizens, and these buildings are likely to have a complex acoustic environment. Previous studies have focused on reducing people's exposure to excessive sound levels caused by transportation, but more research is needed to assess people's preferences and ensure their psychophysical wellbeing. The aim of this study was to explore the complex aspects of the sound environment in large railway stations that contribute to acoustic comfort. On-site measurements and an acoustic comfort survey were performed at a case study site in Harbin, China. The results showed a significant positive correlation between the subjective comfort evaluations and objective measurements of the sound pressure level and reverberation time. Differences in dominant sound sources in different spaces lead to different evaluations of acoustic comfort. People prefer broadcast sound, but its intelligibility needs to be improved. When the density of people increases, the preference for speech sounds and activity sounds decline rapidly. With regard to demographic and social factors, older people and people with higher incomes and education levels are more tolerant of the environment. As railway transportation has become modernized, large railway stations now play an important role in civic architecture. The aim of this study was to explore the effects of sound sources on the sound environment and acoustic comfort in such an extra-large space. Based on subjective and objective measurements of a typical railway station in China that has an extra-large space and multiple sound sources, the effects of sound sources in different functional zones were studied. The overall acoustic comfort and sound pressure levels were related to the sonic composition of the sound sources. The roles of various individual sound sources were investigated, including the speech sounds of other passengers in the seating area, the speech sounds of staff, the sounds of placing luggage in the security scan machine in the security check area, the sounds of a ticket machine in the ticket lobby, and the speech sounds of restaurant workers. The sound sources that have dominant impacts on the survey participants' evaluations of acoustic comfort were determined. In terms of acoustic comfort, broadcast sound was the most preferable, whereas mechanical noise and luggage noise were the least preferable. The sound levels of speech, the intelligibility of both broadcast and speech sounds, and the loudness of the three dominant sound sources exhibited a linear correlation with the sound pressure level. In terms of the effect of the sound characteristics on acoustic comfort, the sound level of speech was the dominant factor. Overall, acoustic comfort can be effectively improved by better planning of the combination and arrangement of sound sources.